Análise da sazonalidade e impacto dos vírus respiratórios em pacientes pediátricos internados em hospital de referência no Paraná - Neves, Elis Renata Filus (2017)
Acute respiratory infections are the most important cause of children morbidity and mortality worldwide. Some of these infections can result in Severe Acute Respiratory Syndrome (SARS). Respiratory viruses are primarily responsible for SARS. The monitoring and surveillance of SARS and respiratory viruses are important for health management, minimizing the impact of these respiratory infections. The present study was about the seasonality and clinical impact of respiratory viruses in children admitted to a pediatric reference hospital. The study included 229 children from 0 to 15 years old, from January 2012 to December 2015, with clinical diagnosis of SARS and respiratory sample collected and sent to the Central Laboratory of the State of Paraná for etiological agent analysis. The search for SARS cases was performed using the GSUS (Health Care Management of SUS) electronic filesystem, records of the center of physiotherapy and information of the Hospital Infection Control Center of the studied hospital. Of the patients included in the research, data collection forms were filled out and later analyzed according to the research objectives. Statistical analyzis were performed with the statistical package GRAPHPAD PRISM and a significance level of 5% was considered. The majority of patients in the sample belonged to the age group 0-6 months of age, and there was no predominant sex. Regarding the risk factors for viral infection, the presence of comorbidity or underlying disease was the most prevalent factor. In the present study, the positive samples for at least one etiological agent accounted for 76.41%, and the most prevalent virus was Respiratory Syncytial Virus (RSV). As for the seasonality of viral detection, there was a predominance in the late fall and early winter, which was more pronounced for RSV. When the environmental temperatures of the region were analyzed, the incidence of SARS was significantly higher in the descending quartile of the average minimum temperature. No significant difference was observed between the studied etiological groups in relation to the time from the beginning of the symptoms until the hospitalization. There was a predominance of hospitalizations in the Intensive Care Unit. The hospitalization time was significantly higher in patients with underlying disease or comorbidities and did not change according to the identified etiological agents or the presence of codetection. Patients who presented a mixed pattern on chest radiography had a significantly longer hospitalization time than those who had the interstitial infiltrate pattern. The total time was significantly lower in the Metapneumovirus group than in the Bordetella pertussis, Influenza, Rhinovirus and group of patients without detected infectious agents. Most patients were discharged from hospital, but there were three deaths due to SARS, all in patients with some underlying disease or risk conditions.